Glucose Increases the Abundance of Phosphate Solubilizing Bacterial Community for Better Apple Seedling Growth and Phosphate Uptake - Zhihang Jia; Lin Zhao; Jia Zhang; Wei Jiang; Meng Wei; Xinxiang Xu; Yuanmao Jiang; Shunfeng Ge (Agronomy, 2022)
Phosphorus-solubilizing microorganisms play an important role in soil nutrient phosphorus cycling. In order to clarify the effect of glucose (C6H12O6) on soil phosphorus transformation, the effects of glucose additions on the bacterial community, soil phosphorus status, and plant phosphorus uptake in apple rhizosphere soil were investigated. A 90-day pot experiment was carried out, and the experiment was repeated three times. Glucose additions were 0, 2.5, 5, 7.5, 10, and 12.5 g glucose per kg of soil. We measured soil bacteria and phosphorus related indexes using Illumina MiSeq sequencing technology and chemical methods. The results showed that when the glucose application rate was 2.5–7.5 g·kg−1, the soil total phosphorus content decreased by 4.4–7.3%; however, the soil acid phosphatase activity increased by 0.5–1.3 times, and the microbial biomass phosphorus increased by 29.1% and 37.0%. The content of Al-P and Fe-P in the rhizosphere soil decreased by 14.4 to 32.7 mg·kg−1 and 16.04 to 28.7 mg·kg−1, respectively. The compositional difference of the bacterial community became larger, and the relative abundance of 11 bacterial phyla changed significantly, among which the most significant change was found in Proteobacteria. This study also found that the relative abundances of Bacillus, Pseudomonas, Arthrobacter, and Cuprococcus increased by 0.9%, 2.2%, 2.4%, and 0.8%, respectively. Applying 7.5 g glucose per kg of soil can significantly increase the relative abundance of phosphorus solubilizing bacteria (Bacillus, Pseudomonas, Arthrobacter et al.) in rhizosphere soil, activate Al-P and Fe-P, and improve the availability of soil phosphorus.